Characterisation of potholes formed on bedrock sandstones at Loei Dun, Phetchabun Geopark, Thailand - Singtuen, Vimoltip; Junjuer, Thitaree (Geologos, 2022)
Phetchabun National Geopark comprises varied geosites; one of the fluvial bedrock landforms distinguished here is Loei Dun. This shows many potholes in Mesozoic sandstone of the Nam Phong Formation (Khorat Group). A genetic study of the occurrence of the Loei Dun potholes lends it a higher geoheritage value. For the present study we did field- work and carried out petrographical and geotechnical analyses so as to classify and characterise the potholes and con- sider geotourism potentials. Petrographically, the bedrock sandstone is a lithic arenite which consists of 82-96 percent very fine to coarse, well-sorted subangular sand with low sphericity and calcite cementation. Our geotechnical analysis of the bedrock sandstone suggests that pothole occurrence may be linked to low rock strength and slake durability index with high rock absorption and porosity at Loei Dun. Field studies confirmed the impact of other factors such as joints/faults, fluvial conditions and biological weathering. There are five types of pothole, viz., simple ones, potholes with external furrows, compound potholes, breached potholes and lateral ones. The present study adds educational value to the Loei Dun geosite at Phetchabun Geoparks and cultural and economic aspects can be further strengthened through the development of geotourism in the area.